2020
DOI: 10.13080/z-a.2020.107.013
|View full text |Cite
|
Sign up to set email alerts
|

Development of herbicides resistance in Apera spica-venti in Lithuania

Abstract: For decades, farmers have been increasingly reliant on herbicides for effective weed management. Repetitive longterm application of herbicides with the same mode of action has resulted in the evolution of herbicide resistance woldwide. The crops most affected by weed resistance in Europe are winter cereals, and one of the worst weeds is silky bent grass (Apera spica-venti (L.) P. Beauv.). Seeds of A. spica-venti were collected from across Lithuania from the farmer's fields, where this weed was not controlled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One of the most important annual grass weeds of winter wheat in Central, Eastern, and Northern Europe is silky bentgrass or bentgrass (Apera spica-venti (L.) P. Beauv) [9][10][11][12][13][14]. The susceptible biotypes of bentgrass pose a significant competitive threat to crops, especially winter wheat [15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important annual grass weeds of winter wheat in Central, Eastern, and Northern Europe is silky bentgrass or bentgrass (Apera spica-venti (L.) P. Beauv) [9][10][11][12][13][14]. The susceptible biotypes of bentgrass pose a significant competitive threat to crops, especially winter wheat [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research confirmed resistant populations of silky windgrass to iodosulfuron and fenoxaprop ethyl ester in Denmark (Babineau et al 2017). In Lithuania, several silky windgrass populations were found resistant to sulfosulfuron (Auskalniene et al 2020). In Czech Republic, silky windgrass populations with varying levels of resistance to herbicides inhibiting ALS, acetyl-CoA carboxylase (ACCase), and photosystem-II (PSII) were confirmed (Kosnarova et al 2021).…”
Section: Introductionmentioning
confidence: 90%
“…Although, it is also found in North European countries, such as Denmark, Sweden and Lithuania (e.g. Auškalniené et al, 2020). It can be controlled with numerous herbicides, including ureas, dinitroanilines and thiocarbamates.…”
Section: Introductionmentioning
confidence: 95%